THE EFFECT OF DIFFERENTIATION LEARNING APPROACH WITH ACROSTIC TECHNIQUE ON POETRY MATERIAL IN IMPROVING LEARNING OUTCOMES OF GRADE V STUDENTS OF SDN LAMKUNYET ACEH BESAR - Wulandari, Annisa; Ahadin, Ahadin; Fitri, Aida (Universitas Syiah Kuala, 2025)
Differentiated learning is learning that is developed to respond to the needs of different students in the learning process. The ability to write poetry here is combined with acrostic techniques. The acrostic technique can be used as a learning strategy to increase motivation to work and at the same time as an alternative to make things easier for students. The research aims to determine the increase in poetry writing abilities and student learning outcomes. This research was conducted in the even semester of the 2023/2024 academic year at Lamkunyet State Elementary School. The type of research used is classroom action research (PTK) or Classroom Action Research using 3 cycles. Data were analyzed using quantitative and qualitative analysis techniques. The results of the research showed that there was an increase in the ability to write poetry in class V of Lamkunyet State Elementary School. The application of the acrostic technique in improving learning to write poetry shows an improvement from moderate to very good criteria. The results of the research show that student learning outcomes increase due to the influence of differentiation learning on poetry material using the acrostic technique. There was an increase of 25.94% in learning outcomes, from the initial condition of 30.66% to 56.60%. The final results of this research show that differentiation learning using acrostic techniques is very influential in increasing students' competence in poetry writing skills.